Dermoscopy of onycholysis due to nail psoriasis, onychomycosis and trauma: A cross sectional study in skin of color - Balachandra S Ankad; Aakash Gupta; Rallapalli Alekhya; Morlawar Saipriya (Wolters Kluwer Medknow Publications, 2020)
Background: Clinical differentiation of onycholysis due to various etiologies is difficult task that compels to do invasive investigations to arrive at accurate diagnosis. Wrong diagnosis often leads to treatment failure and physicians and patient's anxiety. Dermoscopic patterns in nail psoriasis, onychomycosis are well established. Here, authors attempted to describe dermoscopic patterns in onycholysis due to psoriasis, onychomycosis and trauma in skin of color. Methodology: Study was conducted in a tertiary hospital in Southern India. Ethical clearance and informed consent from patients was obtained. Sixty consecutive patients who attended dermatology outpatient department with onycholysis were included in the study. Nail potassium hydroxide (KOH) study was done in all the cases. Onychoscopy was done with DermLite 3 with ultrasound gel as interface medium. Results: Totally 60 patients (42 males; 18 females) with onycholysis were included. Mean age was 37 years (range; 6-68 years). KOH was positive in 22 (36.6%) cases. Onychoscopy showed proximal erythematous rim, red dots, splinter hemorrhages in 23(65.71), 26 (74.28) and 21(60) in nail psoriasis respectively. Spiked and jagged-edges, aurora borealis and ruins pattern (65%) suggestive of onychomycosis were seen in 18(90%), 17 (85%) and 13 (65%) patients respectively. Plain edges without erythema or spikes were noted in 5 (8.33%) in traumatic onycholysis group. Conclusion: Onychoscopy is a non- invasive modality to diagnose psoriasis, onychomycosis and traumatic involvement of nail apparatus by demonstrating characteristic patterns. Hence, it also plays an important role in effective management of such cases.